Understanding the Nature of Hybrid Sterility and Divergence of Asian Cultivated Rice - Zhang, Yu; Wang, Jie; Pu, Qiuhong; Yang, Ying; Lv, Yonggang; Zhou, Jiawu; Li, Jing; Deng, Xianneng; Wang, Min; Tao, Dayun (Frontiers in Plant Science, 2022)
Hybrid sterility is a common form of postzygotic reproductive isolation in hybrids between subspecies of Asian cultivated rice, it is also the major obstacle to utilize the strong intraspecific heterosis in rice breeding program. Here, we review recent progress in classification and hybrid sterility in Asian cultivated rice. Genome-wide analysis of numerous wild relatives of rice and Asian cultivated rice has provided insights into the origin and differentiation of Asian cultivated rice, divided Asian cultivated rice into five subgroups. A lot of conserved and specific loci were identified to be responsible for the hybrid sterility between subgroup crosses by genetic mapping, which also contributed to divergence of Asian cultivated rice. Most of studies focused on the sterile barriers between indica and japonica crosses, ignoring hybrid sterility among other subgroups, led to neither comprehensive systematic understanding the nature of hybrid sterility and subgroup divergence, nor effective utilization of strong heterosis between subgroups in Asian cultivated rice. Future studies should aim at identifying and characterizing genes for hybrid sterility and segregation distortion, comparing and understanding the molecular mechanism of hybrid sterility, and drawing a blueprint for intraspecific hybrid sterility of cross combinations among the five subgroups. These studies would provide scientific and accurate guideline for overcoming the intraspecific hybrid sterility according to the parent subgroup types, allowing utilizing heterosis among subgroups, also helping us unlock the mysterious relationship between hybrid sterility and Asian cultivated rice divergence.